Hunters versus hunted: New perspectives on the energetic costs of survival at the top of the food chain. (7th October 2020) - Williams, Terrie M.; Peter‐Heide Jørgensen, Mads; Pagano, Anthony M.; Bryce, Caleb M.
Abstract: Global biotic and abiotic threats, particularly from pervasive human activities, are progressively pushing large, apex carnivorous mammals into the functional role of mesopredator. Hunters are now becoming the hunted. Despite marked impacts on these animals and the ecosystems in which they live, little is known about the physiological repercussions of this role downgrading from ultimate to penultimate predator. Here we examine how such ecological role reversals alter the physiological processes associated with energy expenditure, and ultimately the cost of survival during peak performance. Taxonomic group, preferred habitat and domestication affected the capacity of the oxygen pathway to support high levels of aerobic performance by carnivorous mammals. Fear responses associated with anthropogenic threats also impacted aerobic performance. Allometric trends for three energetic metrics [maximum oxygen consumption, field metabolic rates (FMRs) and the cost per stride or stroke], showed distinct trends in aerobic capacity for different evolutionary lineages of mammalian predators. Cursorial canids that chase down prey demonstrated the highest relative maximum oxygen consumption rates (10–25 times resting levels) and FMRs, while ambush predators (i.e. felids) and diving marine mammals had aerobic capacities that were similar to or lower than sedentary domestic mammals of comparable size. The maximum energetic cost of performance for apex predators depended on whether the animals were hunters or the hunted. Escape responses were exceptionally costly for marine (narwhal Monodon monoceros ) and terrestrial (mountain lion Puma concolor ) locomotor specialists, as well as semi‐aquatic (polar bear Ursus maritimus ) species; all showed a nearly two‐fold increase in peak energy expenditure when avoiding threats. As the duration and frequency of threats to wild species continue to grow, cumulative energetic costs are becoming more apparent. In view of this, attention to the energy demands of apex predators will provide vital predictive power to anticipate mismatches between a species' functional design and human‐induced pressures, and allow for the development of conservation strategies based on how species are built to survive. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.